MORPHOLOGICAL AND MORPHOMETRIC CHANGES IN THE MARGINAL AND CENTRAL AREAS OF BURN WOUND AFTER EXPERIMENTAL THERMAL TRAUMA - Крамар, С.Б. (World of Medicine and Biology, 2015)
In experiment on guinea pigs morphological and morphometric changes of the damaged area of the skin were studied at different times after severe thermal trauma. It was established that the degree of destructive changes of the epidermis and dermis depends on the period after the burn. Significant vascular disorders and damages of the structural components of skin connective tissue slow down regenerative processes both in the central and in the marginal area of the wound, as evidenced by microscopic observation and morphometric parameters.
Keywords: morphological and morphometric changes; wound; thermal trauma